Analysis of the effectiveness of digital da'wah in promoting islamic lifestyles and psychological well-being among muslim generation z - Laela Arum Baedhun Janna; Rizky Fahmi (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This paper examines the effectiveness of digital da‘wah in promoting Islamic lifestyles and psychological well-being among Muslim Generation Z, a generation that has grown up alongside digital technology and is characterized by dynamic and creative traits. Digital da‘wah utilizes social media platforms such as YouTube, Instagram, and TikTok to convey religious messages in an interactive and contextual manner, enabling adaptation to the needs and lifestyles of Generation Z. Methods: A qualitative descriptive writing approach with a literature study design was employed, in which data were collected from various secondary sources, including national and international journals as well as contemporary digital da’wah content, and then analyzed using content analysis techniques to describe the phenomena and relationships among digital da’wah, Islamic values, and psychological well-being. Findings: The results of the study indicate that digital da‘wah is effective in enhancing religious understanding, shaping Islamic behavior, and improving psychological well-being through creative, empathetic content that is relevant to the everyday lives of Generation Z. Conclusion: Digital da’wah can serve as a strong and adaptive strategic tool for shaping a healthy Islamic way of life and supporting psychological well-being, provided that it is continuously developed in a creative and critical manner to effectively address the challenges and needs of the modern Muslim youth. Novelty/Originality of this article: This study renews the paradigm of da’wah by emphasizing that digital da’wah is not limited to the dissemination of religious teachings, but also functions as a medium for continuous spiritual and psychological guidance. These findings make an important contribution to the development of modern da’wah strategies that are relevant and effective for Muslim Generation Z in the digital era.